2023
DOI: 10.1093/function/zqad017
|View full text |Cite
|
Sign up to set email alerts
|

Lymphatic contractile dysfunction in mouse models of Cantú Syndrome with KATP channel gain-of-function

Abstract: Cantú Syndrome (CS) is an autosomal dominant disorder caused by gain-of-function (GoF) mutations in the Kir6.1 and SUR2 subunits of KATP channels. KATP overactivity results in a chronic reduction in arterial tone and hypotension, leading to other systemic cardiovascular complications. However, the underlying mechanism of lymphedema, developed by > 50% of CS patients, is unknown. We investigated whether lymphatic contractile dysfunction occurs in mice expressing CS mutations in Kir6.1 (Kir6.1[V65M]) or S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…A prominent example of the former is the loss of contractile ability in lymphatic beds that have been irradiated during cancer treatment. The latter is exemplified by Cantú syndrome, which Davis et al (2023) have shown in a mouse model stems from a gain-of-function mutation in one particular ion channel in the LMC pacemaker. The resulting loss of pumping capability leads to lymphoedema in >50% of Cantú syndrome patients.…”
Section: Introductionmentioning
confidence: 99%
“…A prominent example of the former is the loss of contractile ability in lymphatic beds that have been irradiated during cancer treatment. The latter is exemplified by Cantú syndrome, which Davis et al (2023) have shown in a mouse model stems from a gain-of-function mutation in one particular ion channel in the LMC pacemaker. The resulting loss of pumping capability leads to lymphoedema in >50% of Cantú syndrome patients.…”
Section: Introductionmentioning
confidence: 99%
“…LMCs are known to express Kcnj8 (ATP sensitive potassium channel Kir6.1) across multiple species and Kcnj11 (protein Kir6.2) is expressed in some LMC populations (Davis et al, 2022). Cantú syndrome, which has a lymphedema phenotype, can be caused by mutations in the genes Kcnj8 or ABCC9 (Davis et al, 2023a). We observed the expression of Kcnj8, Kcnj11, Abcc8, and Abcc9 genes in a small subset of LMCs (Figure S5D).…”
Section: Potassium Channelsmentioning
confidence: 86%
“…Contraction waves in the lymphatic muscle layer are normally entrained across one or more lymphangions and the degree of entrainment is a critical determinant of the peak internal pressure developed in lymphatic systole 6 . If KCNH2 mutations result in reduced LMC excitability, they will impair contraction wave entrainment 43 and could compromise effective pumping. This consequence of reduced ERG channel activity is predicted to become particularly evident when lymph is transported against an adverse pressure gradient, as we have documented in other contexts 6, 44 .…”
Section: Discussionmentioning
confidence: 99%